Stigma and Quality of Life Among Pre-elderly with HIV in Jakarta, Indonesia - Evanina Alice Pakpahan; Surilena Surilena; Nicholas Hardi (Althea Medical Journal, 2025)
Background: The quality of life (QoL) of people living with HIV (PLWHIV) is affected by physical, psychological, social, and spiritual aspects. During the pre-elderly period (ages 45–59 years), these aspects become major challenges. Stigma is one of the social aspects that may be related to QoL among PLWHIV. This study aimed to examine the correlation between stigma and QoL among pre-elderly with HIV.